a) = x2 + 2x + 3x + 6 = x( x + 2 ) + 3( x + 2 ) = ( x + 2 )( x + 3 )
b) = x2 - x + 4x - 4 = x( x - 1 ) + 4( x - 1 ) = ( x - 1 )( x + 4 )
c) = ( x2 - 10x + 25 ) - 9 = ( x - 5 )2 - 32 = ( x - 8 )( x - 2 )
d) = 6x2 - 15x + 8x - 20 = 3x( 2x - 5 ) + 4( 2x - 5 ) = ( 2x - 5 )( 3x + 4 )
a) x2 + 5x + 6 = x2 + 2x + 3x + 6
= x(x + 2) + 3(x + 2) = (x + 3)(x + 2)
b) x2 + 3x - 4 = x2 - x + 4x - 4 = x(x - 1) + 4(x - 1) = (x + 4)(x - 1)
c) x2 - 10x + 16 = x2 - 2x - 8x + 16 = x(x - 2) - 8(x - 2) = (x - 8)(x - 2)
d) 6x2 - 7x - 20 = 6x2 + 8x - 15x - 20 = 2x(3x + 4) - 5(3x + 4) = (2x - 5)(3x + 4)
a.\(x^2+5x+6=x^2+2x+3x+6=x\left(x+2\right)+3\left(x+2\right)=\left(x+3\right)\left(x+2\right)\)
b.\(x^2+3x-4=x^2+4x-x-4=x\left(x+4\right)-\left(x+4\right)=\left(x-1\right)\left(x+4\right)\)
c.\(x^2-10x+16=x^2-8x-2x+16=x\left(x-8\right)-2\left(x-8\right)=\left(x-2\right)\left(x-8\right)\)
d.\(6x^2-7x-20=6x^2-12x+5x-20=6x\left(x-4\right)+5\left(x-4\right)=\left(6x+5\right)\left(x-4\right)\)
Trả lời:
a, x2 + 5x + 6 = x2 + 2x + 3x + 6 = x ( x + 2 ) + 3 ( x + 2 ) = ( x + 2 )( x + 3 )
b, x2 + 3x - 4 = x2 - x + 4x - 4 = x ( x - 1 ) + 4 ( x - 1 ) = ( x - 1 )( x + 4 )
c, x2 - 10x + 16 = x2 - 8x - 2x + 16 = x ( x - 8 ) - 2 ( x - 8 ) = ( x - 8 )( x - 2 )
d, 6x2 - 7x - 20 = 6x2 - 15x + 8x - 20 = 3x ( 2x - 5 ) + 4 ( 2x - 5 ) = ( 2x - 5 )( 3x + 4 )